The Association Between Amygdala Subfield-Related Functional Connectivity and Stigma Reduction 12 Months After Social Contacts: A Functional Neuroimaging Study in a Subgroup of a Randomized Controlled Trial - Nakamura, Yuko; Okada, Naohiro; Ando, Shuntaro; Ohta, Kazusa; Ojio, Yasutaka; Abe, Osamu; Kunimatsu, Akira; Yamaguchi, Sosei; Kasai, Kiyoto; Koike, Shinsuke (Frontiers in Human Neuroscience, 2020)
Social contact is one of the best methods for reducing stigma, and the effect may be associated with emotional response and social cognition. The amygdala is a key region of these functions and can be divided into three subregions, each of which has a different function and connectivity. We investigated whether the amygdala subregion-related functional connectivity is associated with the effect of anti-stigma interventions on reducing mental health-related stigma in a randomised controlled trial (RCT) over 12 months. Healthy young adults (n = 77, age, mean [S.D.] = 21.23 [0.94] years; male, n = 48), who were subsampled from an RCT (n = 259) investigating the effect of anti-stigma interventions, using filmed social contacts (FSC) or internet self-learning (INS), on reducing stigma, underwent 10-min resting-state functional magnetic resonance imaging between the trial registration and 12 months follow-up. The extent of stigma was assessed at the baseline, post-intervention and 12-month follow-up surveys, using the Japanese-language version of the Social Distance Scale (SDSJ), to assess negative emotional attitude toward people with schizophrenia. We compared associations between amygdala subregion-related functional connectivity and changes in the SDSJ scores for 12 months across the control, INS, and FSC groups. Associations between the change in stigma for 12 months and the superficial (SF) subregion of the amygdala-related connectivity in the intracalcarine cortex ([x, y, z] = [-8, -66, 12], z = 4.21, PFWE-corrected = 0.0003, cluster size = 192) differed across groups. The post-hoc analysis showed that the SF–intracalcarine cortex connectivity was negatively correlated with the change in stigma only in the FSC group. The current results indicate that greater SF–intracalcarine cortex connectivity is associated with a better response to the FSC interventions, suggesting that biological variability could underlie the long-term effect of anti-stigma interventions on stigma in the real world.